Application of 3D printed fixtures for welding - Knezevic, Ivan; Bojic, Savo; Lukic, Dejan; Rackov, Milan; Cavic, Maja; Pencic, Marko; Cako, Sabolc (Journal of Production Engineering, 2019)
3D printing is also known as additive manufacturing (AM). Additive Manufacturing is the manufacturing of products by the addition of layers of material. Additive Manufacturing, in comparison with conventional production processes where the material is taken from workpiece, enables the manufacturing of parts with a minimum quantity of material. 3D printing is often used for rapid prototyping. This paper presents the application of 3D printing for the manufacturing of fixture for welding, in case of welding two parts that form a spatial angle whose accuracy affects the quality of the product's work. The fixture is used for welding the disc support on the agricultural machine, stublle cultivator. This paper presents the procedure of 3D modeling of fixture, preparing for 3D printing and setting the printing parameters. The fixture is printed using the 3D printer Makerbot Replicator 2X from ABS plastic. ABS plastic was selected due to better mechanical properties at higher temperature in relation to PLA material.